Mengenal Matematika dalam Perspektif Islam - Mualimul Huda; Mutia Mutia (Fokus)
The science of Islam sourced from the Qur'an and Hadith should not be positioned in a place apart from other clusters of science, but should be put as a source of knowledge. The Qur'an and Hadith as the source of Islamic teachings serve as guidance (al-huda), explanation (at-tibyan), differentiator (al-furqan), and even healer (as-syifa'). There are many mathematical studies in the Qur'an that describe the science integrated in the Qur'an. One of the Qur'an explains about mathematical concepts such as set, line, calibrate, integer, fraction, and circle. Mathematics is a central science in everyday life and mathematics has been introduced early on. Mathematics is the language used in the creation of the universe. Thus, to learn and understand the verses of Kauniyyah is necessary mathematics. Understanding of the universe will lead to the awe of the power of Allah SWT. In addition, mathematics is also capable of providing a deeper approach to understanding Qawliyyah verses. Muslim scientists contribute thoughts and findings on mathematics. This proves that there is no dichotomy between science and religion.